A Narrative Review of Network Studies in Depression: What Different Methodological Approaches Tell Us About Depression - Wichers, Marieke; Riese, Harriëtte; Hodges, Taylor M.; Snippe, Evelien; Bos, Fionneke M. (Frontiers in Psychiatry, 2021)
The network theory of psychopathology proposes that mental disorders arise from direct interactions between symptoms. This theory provides a promising framework to understand the development and maintenance of mental disorders such as depression. In this narrative review, we summarize the literature on network studies in the field of depression. Four methodological network approaches are distinguished: i) studies focusing on symptoms at the macro-level versus ii) on momentary states at the micro-level, and iii) studies based on cross-sectional versus iv) time-series (dynamic) data. 56 studies were identified. We found that different methodological approaches to network theory yielded largely inconsistent findings on depression. Centrality is a notable exception: the majority of studies identified either positive affect or anhedonia as central nodes. To aid future research in this field, we outline a novel complementary network theory, the momentary affect dynamics (MAD) network theory, to understand the development of depression. Furthermore, we provide directions for future research and discuss if and how networks might be used in clinical practice. We conclude that more empirical network studies are needed to determine whether the network theory of psychopathology can indeed enhance our understanding of the underlying structure of depression and advance clinical treatment.